A study on the development of the flow distortion downstream of an s-duct intake - Migliorini, Matteo; Zachos, Pavlos K.; MacManus, David G.; Monnier, Vianney (International Council of the Aeronautical Sciences (ICAS), 2022)
The use of complex intakes (S-ducts) can enable a closer integration between the airframe and the propulsion system to target a reduction of aircraft fuel consumption, noise, drag, and emissions. However, these advantages may be offset by the increased unsteady flow distortion that arises which can adversely affect the aero-engine. This is also of interest where non-uniform conditions are present at the inlet, for example in Boundary Layer Ingestion (BLI) aircraft. The flow distortion may result in a reduction of the operability range of the engine and in a risk for the development of new propulsion systems. Recently, high-bandwidth Particle Image Velocimetry (PIV) and the statistical modelling of extreme events have been used to assess the S-duct flow distortion. In this work, these methods are used to assess the development of the flow distortion characteristics downstream of the S-duct outlet plane. Non-uniform conditions at the inlet of the S-duct intake produced a sharp growth of the peak distortion levels which is attributed to the increase of local flow unsteadiness that could be linked to the secondary S-duct separation. These peak distortion levels were identified through the modelling of extreme events where the growth of the peak distortion levels was projected beyond the experimental observations. Overall, this work highlights the importance of statistical modelling of the unsteady distortion and shows the development of the unsteady swirl distortion levels downstream of the S-duct outlet plane.
© The Author.
Keywords: Intake; Flow distortion; Aero-engine; Unsteady; Swirl